Improvement of the synthetic tri-peptide vaccine (S3Pvac) against porcine Taenia solium cysticercosis in search of a more effective, inexpensive and manageable vaccine - Sciutto, Edda (2006)
Vaccination of pigs may curtail Taenia solium transmission by reducing the number of cysticerci, the precursors of adult intestinal tapeworms in humans. Several antigen preparations induce protection against porcine cysticercosis in experimental settings but only one subunit vaccine (S3Pvac) has been tested and proved effective in the field against naturally acquired disease. Besides improving of the vaccine's effectiveness, significant reductions in production costs and in the logistics of its administration are necessary for the feasibility of nationwide control programs. This review highlights the development of several versions of S3Pvac aimed to increase effectiveness, reduce costs and increase feasibility by novel delivery systems and alternative routes of administration